Molecular detection of Potential Novel Mansonella species (Filarioidea: Onchocercidae) in equine and Culicoides enderleini from Africa - Sadeddine, R; Sambou, M; Davoust, B; Righi, S; Daghri, K; Benakhla, A; Parola, P; Mediannikov, O (Journal of the Hellenic Veterinary Medical Society, 2024)
A new genotype of a filarial worm from the Mansonella genus was determined in three donkeys from Algeria, as well as from four horses and two Culicoides enderleini biting midges from Senegal. Phylogenetic analysis based on the ITS1 and rRNA 5S genes shows similar results clustering this filarial worm within the genus Mansonella with low identity with all known Mansonella species. Further research should be performed to characterise this Mansonella sp. and assess its prevalence in African countries.